Arrhythmogenic cardiomyopathy with left ventricular involvement versus ischemic heart disease: lessons learned from the family study and the reviewed autopsy of a young male - Pilar Molina; Jorge Sanz-Sánchez; Manuel Fenollosa; Marina Martínez-Matilla; Juan Giner; Esther Zorio (Oxford University Press, 2019)
Ischemic heart disease (IHD) is the leading cause of sudden cardiac death (SCD) and often non-thrombosed severe coronary stenoses with or without myocardial scars are detected. Left dominant arrhythmogenic cardiomyopathy (LDAC) is a life-threating rare disease which has been more thoroughly studied in the last 10 years. The macroscopic study of an SCD victim was conducted and re-evaluated 9 years later. The cardiological work-up in his first-degree relatives initially comprised an electrocardiogram (ECG) and an echocardiogram. When they were re-evaluted 9 years later, a cardiac magnetic resonance, an ECG-monitoring, an exercise testing and a genetic study were performed and the pedigree was extended accordingly. In 2008, an IHD was suspected in the sports-triggered SCD of a 37-year-old man upon the postmortem (75% stenosis of the left main and circumflex coronary arteries; the subepicardial left ventricular fibrofatty infiltration with mild myocardial degeneration was assumed to be a past myocardial infarction). No cardiomyopathy was identified in any of the two proband's sisters. Nine years thereafter, distant relatives were diagnosed with LDAC due to a pathogenic desmoplakin mutation. The reanalysis of the two sisters showed ventricular arrhythmias in one of them without structural heart involvement and the reviewed postmortem of the proband was reclassified as LDAC based on the fibrofatty infiltration; both were mutation carriers. The completion of the family study on 19 family members yielded one SCD due to LDAC (the proband), three living patients diagnosed with LDAC (two with a defibrillator), one mutation carrier without structural ventricular involvement, and 14 healthy relatives (who were discharged) with a very good co-segregation of the mutation. Although rare, LDAC exists and sometimes its differential diagnosis with IHD has to be faced. Modifying previous postmortem misdiagnoses can help family screening to further prevent SCDs.